The Influence Of Leadership Style And Organizational Culture On Employee Performance In The Moderation Of The Work Climate In The Office Bank Indonesia Provincial Representative North Sumatra - Muhammad Khairul Ibaad Pohan; Mesra B (International Journal of Management, Economic and Accounting, 2024)
This study aims to see the Influence of Leadership Style and Organizational Culture on Employee Performance in Work Climate Moderation at Bank Indonesia Representative Office in North Sumatra Province. Human beings need special attention because they are basically able to develop, have intellect, ideas, feelings, desires, and hopes. These variables also affect achievement, dedication, loyalty, and love for work and the success of the organization. Therefore, human resource managers are indispensable to improve employee performance, so that it is beneficial for the company and able to survive in a competitive and dynamic business climate. The results of this study are as follows: Organizational Culture has a positive and significant effect on Employee Performance with the original sample value of 0.446 and p values of 0.000. The Work Climate could not moderate the Leadership Style on Employee Performance with the original sample value of -0.033 and the p values of 0.420. The Work Climate was not able to moderate the Organizational Culture towards Employee Performance with the original sample value of 0.031 and p values of 0.419. Leadership Style had a positive and insignificant effect on Employee Performance with the original sample of 0.115 and p values of 0.128. Work Climate has a positive and significant effect on Employee Performance with an original sample value of 0.392 and p values of 0.000.